Effect of inner diameter on the confinement of two-phase closed thermosyphon - Kang, Sukkyung; Seo, Jin Hyeuk; Lee, Jungho (International Communications in Heat and Mass Transfer, 2023)
A two-phase closed thermosyphon (TPCT) is a heat transfer device that effectively transfers heat through the phase change of a working fluid. While the working fluid circulates smoothly in a nominal TPCT, compact TCPT has a greater shear force effect between the upward vapor flow and the falling liquid. The inner diameter and type of working fluid significantly affect the confinement effect, but the effects of the inner diameter on the confinement remain unclear. In the case of Co > 0.5, the TPCT was fully confined, so the heat was dominantly transferred by axial conduction through the confined bubbles and liquid slugs. For Co < 0.5, the working fluid circulated smoothly, and the heat was mainlytransferred by latent heat. In the unconfined case, the heat transfer coefficient at the evaporator slightly increased at high Co owing to the mixing effect within the liquid pool. In the condenser, the cold surface was covered with liquid at high Co values owing to the re-rising of falling liquid by the high shear rate. As a result, the overall thermal resistance of the TPCT increased at high Co values due to the significant degradation in the thermal performance of the condenser.
Keywords: Axial conduction; Confinement effects; Force effects; Heat transfer device; Inner diameters; Phase Change; Shear force; Two-phase closed thermosyphon; Vapor flows; Working fluid; Confinement effect; Inner diameter; Two-phase closed thermosyphon